2012 IEEE 12th International Conference on Advanced Learning Technologies 2012
DOI: 10.1109/icalt.2012.144
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Real-Time EEG Analysis for Assessing Flow in Games

Abstract: Ability of adapting to different users is considered key to maximize the impact and effectiveness of Serious Games (SGs). Advances in neurosciences are making it possible to continuously monitor the player status. This paper reports the research work on the monitoring of the player flow status with a simple (4 electrode) commercial electroencephalogram (EEG). In particular, we focus on three consequential research questions: is it possible to statistically distinguish a flow from a boredom condition? For which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Furthermore, new methods to study flow are emerging. Advances in neurosciences are making it possible to continuously monitor the player status [25,26]. Certain dimensions of flow can be validated with functional brain imaging, which can improve the understanding of human emotions and motivational processes during media entertainment [27].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, new methods to study flow are emerging. Advances in neurosciences are making it possible to continuously monitor the player status [25,26]. Certain dimensions of flow can be validated with functional brain imaging, which can improve the understanding of human emotions and motivational processes during media entertainment [27].…”
Section: Related Workmentioning
confidence: 99%
“…In addition to subjective assessment, a growing area of assessment includes a branch of neuroscience that is investigating the correlation between user psychological states and the value of physiological signals. Several studies have shown that these measures can provide an indication of player engagement (see [38][39][40][41]) and flow [42]. Common physiological measures include the following [41,43].…”
mentioning
confidence: 99%
“…Some work [14,18,21] has been done with the theory of Flow [10,8], but this approach remains problematic because the theory is descriptive of subjective states, and not predictive of physiological states. A stronger link can be found in simpler cognitive mechanisms, which may in combination provide an index to HLC/HPC under the right measurement protocol.…”
Section: Discussionmentioning
confidence: 99%